Japan : a comparative view - Craig, Albert M.; Borders, Orin (Princeton legacy library., 1979)
Among the leading specialists on Japan, the authors-both Japanese and Western-represent a range of disciplines from economics, history, and political science, to sociology, anthropology, psychiatry, and literary criticism. Some of the essays draw comparisons with China or Korea, some with England, Europe, or America, and some with countries of the Third World. By showing us how the Japanese experience relates to that of other contexts, the authors provide us with important insights into Japan as well as into other societies undergoing a modern transformation.Originally published in 1979.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.